Improving the quality of learning modules : a continuous process - Halimatolhanin Mohd Khalid,; Zoraini Wati Abas,; Mazlan Zulkifly, (2007)
As an open and distance learning provider, Open University Malaysia (OUM) prioritises the quality of its learning modules. These modules are the primary learning material for OUM’s self-managed students within and outside Malaysia. One of the crucial processes involved in this continuous improvement of learning modules is instructional design. Being accredited as ISO 9001:2000 compliance, the process of instructional design at the Centre for Instructional Design and Technology (CiDT) has not been without challenges. In fact, it is more difficult indeed for instructional designers to justify that quality has always play a major role during the instructional design process. This paper will report on the continuous efforts done to improve on the quality of OUM’s learning materials. What process is considered a success story for one print module may differ from another. Lessons learned and the continuous improvements of the quality of the instructional designers are also discussed in this paper. The findings from this study accentuate further improvement needed for the process. The results of the findings have direct implications on future creation and development of OUM print modules.